Pelvic organ prolapse: anatomical and functional assessment. Issue 7 (July 2022) - Abbas, Nazish; Reid, Fiona
Abstract: Pelvic organ prolapse (POP) is a common presenting complaint in gynaecology. In the UK, prolapse accounts for 20% of women on the waiting list for major gynaecological surgery. It is therefore important that clinicians understand how to accurately assess women with prolapse. The aim of this article is to provide a comprehensive description of the assessment required. Anatomical assessment should be made using the standardized Pelvic Organ Prolapse quantification system (POP-Q). The use of POP-Q in women with POP allows effective communication between clinicians, reproducible evaluation of surgical outcomes, meaningful comparison of published series and comparison of different populations. The main focus of the article is a detailed and practical explanation of the POP-Q.